AD, Volume 8, n° 3, 1983 - Full Issue (Africa Development, 1983)
CONTENTS Développement Agricole et Indépendance Alimentaire Nacer BOURENANE ......................... 5 Class, Gender and Capitalist Transformation in Africa Janet M. BUJRA ........................... 17 The IMF and Africa in the 1980s G.K. HELLEINER ......................... 43 Nigerian Food Shortages: A study of Import Demand for Selected Cereals, 1950—79 A. A. ADESIMI ................................ 62 L'Etat et la Société en Afrique P. ANYANG' NYONGO ..........................75 The Deepening Economie Crisis and its Political Implications Yusuf BANGOURA, Rauf MUSTAPHA & Saidu ADAMU ...... 97 BOOK REVIEW South Africa — A Model Capitalist State? fil. Dr. Howard SIMSON ....................120 FOCUS ON RESEARCH AND TRAINING INSTITUTES The Research Unit of the Department of Town and Country Planning Zambia ................. 124 ANNOUNCEMENT: Justinian F. RWEYEMAMU Memorial AWARD Books Received